Potential of Islamic finance : a survey of Tunisian Northwest companies / Rym Ammar Ayachi, Dhafer Saidane and Fayçal Mansouri - Ammar Ayachi, Rym; Saidane, Dhafer; Mansouri, Fayçal (Faculty of Business and management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2017)
The present paper aims to assess the Islamic products potential demand for entrepreneurs in the Tunisian Northwest region. In order to do so, we developed a questionnaire which was sent to these entrepreneurs. The survey results show that the latter perceive Islamic Finance as a seductive phenomenon. However, its development appears to be difficult. Indeed, according to the survey results, the lack of knowledge may impede the expansion of Islamic banking in Tunisia. Moreover, the following factors:, cost, religious conviction, proximity, flexibility and satisfaction of the needs, may affect the entrepreneurs' choice to deal with Islamic financial institution. In addition, the lack of entrepreneurs' confidence with regard to the compliance of Islamic banking with the Shariah principles has a negative effect on Islamic finance development in the Tunisian Northwest, region. For this reason, Tunisian Islamic banks should put more effort to reinforce their competitiveness.